2011
DOI: 10.1186/1472-6947-11-54
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation of meningioma from non-contrasted brain MRI integrating fuzzy clustering and region growing

Abstract: BackgroundIn recent years, magnetic resonance imaging (MRI) has become important in brain tumor diagnosis. Using this modality, physicians can locate specific pathologies by analyzing differences in tissue character presented in different types of MR images.This paper uses an algorithm integrating fuzzy-c-mean (FCM) and region growing techniques for automated tumor image segmentation from patients with menigioma. Only non-contrasted T1 and T2 -weighted MR images are included in the analysis. The study's aims a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 31 publications
0
53
0
1
Order By: Relevance
“…meningiomas and gliomas. For semi-automated segmentations, various approaches have been applied, such as region growing, random walker, non-negative matrix factorisation, fuzzy clustering and livewire algorithm [20][21][22][23][24]. Automated tumour volume definition has also been applied in post-radiation patients using an algorithm that is based on the Chan-Vese active contour method and patient-specific intensities [25].…”
Section: Introductionmentioning
confidence: 99%
“…meningiomas and gliomas. For semi-automated segmentations, various approaches have been applied, such as region growing, random walker, non-negative matrix factorisation, fuzzy clustering and livewire algorithm [20][21][22][23][24]. Automated tumour volume definition has also been applied in post-radiation patients using an algorithm that is based on the Chan-Vese active contour method and patient-specific intensities [25].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively similar T1 and T2 relaxation parameters among pathologic brain lesions, brain edema, and fibrotic tissue are obtained on T2WI, as compared with CE-T1WI (20). It is also known that the differences in signal intensities among the clusters are not sufficient to separate tumor components, such as solid, cystic, or hemorrhagic components, perilesional edema, and perilesional tumor infiltration, automatically on T2WI (10,22). According to the aforementioned reports, the T2WI-based semiautomatic segmentation method would be less reproducible in the groups with perilesional edema, with poorly demarcated inner margins of the necrotic portion, and with poorly demarcated outer tumor borders.…”
Section: Discussionmentioning
confidence: 99%
“…For those tumor types, the threshold-based segmentation method may be applied to T 1 -weighted or diffusion-weighted images, if the contrast between tumor and other tissue is more visible on those images. While the threshold-based method is likely to require re-definition of the set thresholds for each tumor type, automatic selection of clusters could possibly also be performed on the basis of features more specific to tumors in general, for example shape, size [18], and tissue homogeneity [9]. Recently, Linguraru et al [34] showed that liver tumors can be accurately detected on contrastenhanced computed tomography images by using a set of features that describe the intensity, shape, size, and homogeneity of identified objects of interest in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Hsieh et al [18] reported a method for automatic segmentation of meningiomas on the basis of T 1 and T 2 -weighted images. Although successful segmentation was achieved for most tumors, the method failed in approximately 20 % of cases.…”
Section: Methodsmentioning
confidence: 99%